CoopDynSim : a 3D robotics simulator - Machado, Toni Daniel Neto (2012)
This paper presents CoopDynSim, a multi-robot 3D simulator. The main motivations for the development of a new simulation software lie in the need to emulate specific, custom made sensors, combined with the desire to smoothly transfer controller code from simulation to real implementation. The latter is achieved through the use of the same middleware layer already implemented in the real platforms. The high modularity of the solution allows the user to easily add new components or design new platforms. By having independent simulation threads for each robot, distributed control algorithms can easily be tested, abetted by a socket based connection, granting the possibility for an asynchronous, over the network, controller architecture. The ability to run simulations in real or simulated time, as well as a play back option, represent valuable features of the software. The simulator has been used in several projects, with different platforms and distinct control applications, proving it as a heterogeneous and flexible solution. Furthermore, its usage as a teaching tool in a robotics’ summer school as well as in an introductory robotics class in our university, upholds its simplicity and user-friendliness.